2016
DOI: 10.1016/j.jid.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Susceptibility Loci for Cutaneous Squamous Cell Carcinoma

Abstract: We report a genome-wide association study (GWAS) of cutaneous squamous cell carcinoma (SCC) conducted among non-Hispanic white (NHW) members of the Kaiser Permanente Northern California (KPNC) health care system. The study includes a genome-wide screen of 61,457 members (6,891 cases and 54,566 controls) genotyped on the Affymetrix Axiom European array and a replication phase involving an independent set of 6,410 additional members (810 cases and 5600 controls). Combined analysis of screening and replication ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
148
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(154 citation statements)
references
References 78 publications
5
148
0
1
Order By: Relevance
“…This locus lies 35 kb upstream of HLA-DQB1 , a gene also associated with squamous cell cervical cancer risk [12]. Asgari et al [13] found that HLA locus 6p21 reached genome-wide significance and was strongly associated with cSCC risk. This locus is associated with expression levels of HLA-DQA1 , HLA-DQB1 , and HLA-DRB5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This locus lies 35 kb upstream of HLA-DQB1 , a gene also associated with squamous cell cervical cancer risk [12]. Asgari et al [13] found that HLA locus 6p21 reached genome-wide significance and was strongly associated with cSCC risk. This locus is associated with expression levels of HLA-DQA1 , HLA-DQB1 , and HLA-DRB5 .…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 includes HLA locus 6p21 identified by Asgari et al [13], as it was strongly associated with cSCC risk and the risk ratio per allele was not seen to vary by immunosuppression status. Table 2 also summarizes a reanalysis by Glover et al in 1993 [6] of the data reported in their 1991 study [14], but with some controls reclassified as cSCC cases upon more detailed screening.…”
Section: Resultsmentioning
confidence: 99%
“…Here we report a comparison of these results with those of a previous GWAS involving 7,701 non-Hispanic White (NHW) cSCC patients and 60,186 NHW control subjects in the Kaiser Permanente Northern California (KPNC) health care system (2). …”
mentioning
confidence: 99%
“…Homens residentes no EUA (OR = 0,55, 95% intervalo de confiança [IC] de 0,38-0,80) e Brasil (OR = 0,49, 95% CI 0, 73) foram significativamente menos propensos a serem detectados com algum β-HPV no canal anal, comparado aos residentes no México. A idade foi marginalmente associada à maior prevalência de HPV na região do canal anal sendo que de homens mais velhos (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)OR = 1,30,95% CI 0,82;OR = 1,59,95% CI 0,58) foram mais propensos a serem positivos para DNA de β-HPV, comparado a homens mais jovens (18-30 anos). A prevalência de algum β-HPV na cavidade oral também foi significativamente associada ao país de residência e idade.…”
Section: Lista De Abreviaturas Siglas E Símbolosunclassified
“…Samples were tested for PCR amplification with PGMY09/11 primers, and HPV genotyping was conducted with the Roche Linear Array (Roche Molecular Diagnostics, Alameda, CA, USA), which is able to discriminate 37 α-HPV types (oncogenic types 16,18,31,33,35,39,45,51,52,56,58,59, and 66; non-oncogenic types 6,11,26,40,42,53,54,55,61,62,64,[67][68][69][70][71][72][73][81][82][83][84]IS39,and CP6108) [14]. Samples that tested PCR-positive and Linear Array-negative with all specific HPV probes were considered to be unclassified and included in the present study.…”
Section: Hpv Detectionmentioning
confidence: 99%